Pengaruh Kualitas Pelayanan, Persepsi Harga, dan Promosi terhadap Kepuasan Pelanggan di Mr. Keen Laundry - Reza Nisfu Kharista; Hariadi Hadisuwarno (J-CEKI : Jurnal Cendekia Ilmiah, 2023)
The purpose of this research is to find out how customer satisfaction is at Mr. Keen Laundry is influenced by service quality, price perception, and promotional activities. This study uses a quantitative survey-based research approach with a target sample of 100 respondents. The study makes use of information collected directly from respondents, such as surveys on customer happiness, price perceptions, and service quality. Based on the results of the study, it shows that service quality, price perceptions, and promotions have a significant effect on customer satisfaction either partially or simultaneously. From the results of the determination coefficient of 53.1%, it can be concluded that factors including service quality, price perceptions, and promotional activities have an effect on customer satisfaction, while the remaining 46.9% is influenced by other variables such as product quality, brand perception, etc. The conclusion is service quality, perceived price and promotion are important aspects of customer satisfaction at Mr. Keen Laundry.